Myanmar Agreement in Signing the China-Myanmar Economic Corridor (CMEC) Project - Sonia Mustikasari (Jurnal Multidisiplin Sahombu, 2026)
This research aims to explain the reasons behind Myanmar's decision to sign the China-Myanmar Economic Corridor (CMEC) project with China. The problems raised in this study are related to internal and external dynamics that affect Myanmar's foreign policy stance towards the strategic infrastructure project. This study uses a qualitative approach with literature study methods and explanatory analysis. The adaptive model theory in foreign policy developed by James N. Rosenau is used to analyze Myanmar's response to changes in the domestic and international environment. The results show that Myanmar is under pressure from external factors, such as the global power structure, regional alliances, geopolitical situation, as well as internal factors, such as the need for economic development and increased domestic political accountability. Myanmar shows an acquiescent adaptation pattern, which is a form of foreign policy adjustment that shows a tendency to approve the initiative of the dominant partner country, in this case China. The conclusions of this study show that Myanmar's decision to join the CMEC project is the result of adaptation to a combination of external pressures and internal needs, which makes China a key strategic partner in its national development framework.